(untitled) (Bangladesh Journal of Infectious Diseases, 2023)
Background: Dengue infection is endemic in Bangladesh and presents with varying degrees of severity of illness in children. Objective: The purpose of the present study was to assess the common clinical profile, biochemical findings and outcome of severe dengue fever in children. Methodology: This prospective cohot study was conducted on dengue NS1 or IgM or RT-PCR positive admitted children up to 14 years of age from April 2019 to October 2019 for a period of 6 months at the Pediatrics Department of Evercare Hospital, Dhaka. Data were analyzed after collection of demographic variables, presenting complaints and examination findings of 75 enrolled children. Results: A total of 75 cases were classified as severe dengue fever. The most common age of presentation was 4 to 7 years. The most common presenting symptom of severe dengue cases were fever (97.3%), abdominal pain and vomiting (77.3%) and shock (62.7%). Pleural effusion was the most common physical findings seen in 35 cases (46.6%) followed by ascites in 26 cases (34.7%). Elevation in aspartate amino transaminase AST (IU/L) was found in 82.6%, low albumin was found in 78.7% of the cases. Hypernatremia was the most common electrolyte abnormality found in 35 cases (46.7%). Regarding coagulation profile, raised D-dimer & low fibrinogen were found in 53 (70.7%) & 42 cases (56.0%) respectively. Activated partial thromboplastin time (aPTT) was prolonged in 37.3%. Case fatality rate (CFR) was 5.3%. Conclusion: In conclusion, raised AST and D-dimer, low fibrinogen & albumin level as well as hyponatremia are significant laboratory findings indicating severity of the disease. Shock is a common presentation of severe dengue in children. Bangladesh Journal of Infectious Diseases, December 2022;9(2):40-46